Breach of Contract by The Owner of a Multilevel Marketing Business in International Transactions - Sihite, Sri Rumada; Laturette, Adonia Ivonne; Labetubun, Muchtar Anshary Hamid (Balobe Law Journal, 2026)
Introduction: A multilevel business owner who breaches a promise, or in other words, commits a breach of contract in international transactions, is proven to have breached a promise in this study. This study examines whether the breach of contract by multilevel business owners in international transactions is a deliberate act, a legal act, or the result of information asymmetry, differences in regulations between countries, and weak oversight of multilevel business schemes that fall under jurisdictional authority.Purposes of the Research: To examine the rights of multilevel marketing members in cases of breach of contract by multilevel marketing business owners who fail to fulfill their obligations, or, in other words, in international transactions, as well as the legal consequences of such transactions.Methods of the Research: The research method used is the normative legal method, employing a legislative and conceptual approach.Results of the Research:  Breach of contract by multi-level business owners in international transactions, where such owners have been found to potentially commit breach of contract in the form of a breach of promise—specifically, by failing to pay bonuses or commissions in accordance with the promised scheme to cross-border recipients. The legal consequences of breach of contract refer to Article 1243 of the Civil Code, namely compensation, cancellation of the agreement accompanied by compensation, transfer of risk, and payment of legal costs, but in an international context. The affected members face challenges in the form of a conflict of laws when the contract does not specify a clear choice of law. In this case, compensation is sought in the form of monetary damages.